Youth has the ball at its feet - TUC recruitment leaflet, 1938 (1938)
1938 1918-1939 "Youth has the ball at its feet - TUC recruitment leaflet, 1938" [T0140.jpg], 1938, Trades Union Congress In 1938, the TUC produced a Youth Charter for young workers which demanded the raising of the school leaving age to 16 years, a limit of 40 hours on the working week and the abolition of overtime for under 18s, adequate technical training and 14 days paid holiday each year.